Product Quality Dimensional Analysis of Repurchase Intention - M. Trihudiyatmanto (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2023)
Purpose - This study aims to prove the effect of product performance, product durability and product aesthetics on repurchase intention. Methodology - The data used were interviews and questionnaires that came from direct respondents. The population in this study were consumers of wardah products themselves, namely UNSIQ Central Java students in Wonosobo. The sampling technique used the Rao Ancient Formula. The number of samples in this study were 100 respondents or Central Java UNSIQ students in Wonosobo. The analysis technique used in this research is SPSS. Results - This study shows that product performance (X1) has a positive effect on repurchase intention, product durability (X2) has a positive effect on repurchase intention, product aesthetics (X3) has a positive effect on repurchase intention. Limitations - collecting data in this study using an online questionnaire from here it could be that what the researcher will convey to the respondent becomes an understanding that is not understood. Future Research Agenda - should use interview techniques directly with respondents, so that the results are better and in accordance with the existing reality, assist respondents in filling out questionnaires, can expand other indicators and vary more according to the object of research.